1993
DOI: 10.1007/bf02250880
|View full text |Cite
|
Sign up to set email alerts
|

Feed resource base for scavenging village chickens in Sri Lanka

Abstract: The productivity of a population of scavenging village chickens in Sri Lanka has been assessed, and the scavenging feed resource base has been measured and analysed. The laying period lasted 34 +/- 13 days and the batch size was about 20 eggs. The households ate 71% of the egg production. The mean egg weight was 48 g and the mean size of a set of eggs was 9.4. The hatching percentage was 67 +/- 32 and the liveweight at 70 days averaged 313 g with a range of 142 to 492, by which time 65% of the chicks hatched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 2 publications
0
40
4
Order By: Relevance
“…In the present study the high AME of 12.7 MJ/kg DM to 13.5 MJ/kg DM of crop contents suggests that the fowls had access to diets that were high in energy. These high energy levels are supported by the relatively low CF levels of <40 g CF/kg DM in the crop contents compared with 54 g CF/kg recommended by Gunaratne et al (1993) for commercial hens. High NFE levels (590 to 649 g/kg), indicating soluble carbohydrates, were recorded (Table 3) and support the high ME levels in the crop content.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study the high AME of 12.7 MJ/kg DM to 13.5 MJ/kg DM of crop contents suggests that the fowls had access to diets that were high in energy. These high energy levels are supported by the relatively low CF levels of <40 g CF/kg DM in the crop contents compared with 54 g CF/kg recommended by Gunaratne et al (1993) for commercial hens. High NFE levels (590 to 649 g/kg), indicating soluble carbohydrates, were recorded (Table 3) and support the high ME levels in the crop content.…”
Section: Discussionmentioning
confidence: 98%
“…The availability and composition of the various feed items varied with season. This, as well as, for example, whether it is sowing or harvesting time, has previously been observed to influence the crop contents of scavenging birds (Gunaratne et al, 1993). The higher occurrence of grains found in the crops during the rainy season can be attributed to the fact that the study was carried out at the beginning of the rainy season when farmers were sowing, and when waste grains and seeds were available in the backyard.…”
Section: Crop Content Weights and Physical Characteristicsmentioning
confidence: 93%
“…The scavenging feed resource base is variable, depending on season, location and management. Various authors have reported that the proportion that comes from the environment varies with activities such as land preparation, sowing, harvesting, grain availability in the household, the life cycles of insects or other invertebrates, and the biomass of the village flock (Gunaratne et al, 1993;Dessie and Ogle, 1996;Mwalusanya et al, 2002). The limited supply of nutrients restricts the productive potential of local birds (Dessie and Ogle, 1996); any attempt to supplement local poultry should thus take into consideration estimates of what the birds actually consume.…”
Section: Introductionmentioning
confidence: 99%
“…This could explains the reason for higher grains in the crop contents in early dry season as compared to early and late rainy seasons. Gunarantne et al (1993) and Dessie (1996) have previously observed that the crop contents of scavenging chicken is affected by harvesting and planting periods. The significantly (P<0.05) higher grains in the crop contents of layers as compared to that of growers may be a reflection of the preferential treatment given to the adult birds in grain supplementation by the local people.…”
Section: Discussionmentioning
confidence: 99%